Exploring the Determinants of Chinese Tourists’ Shopping Behavior During Shopping Tourism in Korea - Qizhen Dong; Shuai Ling; Can Zheng; Yan Hu; Feng Lin; Seul Ki Lee (Behavioral Sciences)
This study aimed to examine the factors influencing Chinese tourists’ shopping behavior during shopping tourism in Korea using a theoretical framework based on the modified theory of planned behavior (TPB). A quantitative research method was used; the questionnaire for this study was posted on Wenjuanxing for data collection and 269 valid questionnaires were analyzed in September 2024 using partial least-squares structural equation modeling (PLS-SEM). The results of analyzing the 269 questionnaires showed that attitude, conformity, perceived behavioral control, and perceived quality of goods influenced shopping intention. However, face consciousness did not affect shopping intentions. Additionally, Chinese tourists’ shopping intentions influenced their shopping behavior during shopping tourism in Korea. The results of this study reveal the potential mechanisms of the influence of shopping intentions with conformity (a factor of Chinese-subjective norms) and the perceived quality of goods (a new factor) in shopping behavior, and they provide theoretical guidance and appropriate marketing strategies for companies in the Korean tourism field.